Pitter and Patter - Sullivan, Martha (Dawn Publications, 2015)
"The water cycle becomes a down-to-earth reality when children follow Pitter on his overland journey from cloud to ocean, and Patter on her journey from cloud to ocean by way of an underground route. In the ocean they meet and join in a cloud once again. 'Explore More' endnotes provide additional explanations of water cycle principles"--